Using the Principles from Community of Practice: Developing Sustainable Professional Development Programmes in Physical Education - Daniel Milton; Anna Bryant; Paul R. Appleton; Joan L. Duda (Education Sciences)
Continuing professional development is vital for enhancing teaching quality in Physical Education, but traditional approaches often lack effectiveness. This study explores the implementation of a Community of Practice framework integrated with motivational theory to develop and evaluate a Physical Education professional development programme in a Welsh secondary school, assessing its impact, benefits, challenges, and critical considerations. This 18-month longitudinal qualitative study involved eight staff members. Data were collected through interviews, focus groups, researcher reflections, collaborative discussions, and a WhatsApp group. Deductive thematic analysis was employed. Three main themes emerged: understanding effective continuing professional development and community of practice principles, establishing and maintaining professional development opportunities incorporating community of practice, and evaluating the professional development programme’s impact. A boundary spanner (the principal investigator) played a pivotal role in bridging school and external expertise, by facilitating ongoing collaboration and knowledge exchange within the community of practice. The “boundary spanner” played a critical role in facilitating the use of WhatsApp, which enhanced engagement and sustainability. Teachers reported improved planning, increased collaboration, and enhanced understanding of motivational strategies. This study advances physical education professional development literature by demonstrating the effectiveness of integrating community of practice principles with theory-informed professional development programmes. It emphasises the importance of contextual understanding, theoretical grounding, and the ‘boundary spanner’ role. The findings underscore the need for research-informed, context-specific principles to enhance professional development programmes in PE, highlighting technology’s potential in facilitating ongoing professional development.